CdSe/TiO2 nanotubes for enhanced photoelectrochemical activity under solar illumination: Influence of soaking time in CdSe bath solution - Lai, Chin Wei; Lau, Kung Shiuh; Chou, Pui May (Elsevier, 2019)
In the present study, nanotubular structure of cadmium selenide/titanium dioxide (CdSe/TiO2) was successfully prepared via chemical bath deposition (CBD) chemosynthesis method to improve photoelectrochemical activity under solar illumination. The results revealed that optimum CdSe dopants incorporated into TiO2 nanotubes played a crucial role in determining the photoelectrode performance in water splitting. It was found that synthesized CdSe/TiO2 nanotubes soaked at 30 min of CdSe precursor showed a maximum photocurrent density of 0.0016 A/cm2 with improvement of about 10% than that of pure TiO2 nanotubes under solar illumination. The presence of optimum contents of CdSe dopants incorporated into TiO2 nanotubes could act as efficient mediators for trapping photo-induced electrons and reduce the recombination losses of charge carriers significantly.